Combining Ability Analysis in Indian Mustard: Full, Half And Quarter Diallel Analysis - Jindal, S K (Annals of Arid Zone, 2016)
Combining ability studies, using Methods I, 2, 3 and 4, Model I of Griffling were carried out for seed yield using a 14 x 14 diallel set in Indian mustard. The estimates of both the combining ability variances were significant for all the methods except Method 3 where specific combining ability variance was non-significant. Variances due (0 reciprocal cross effects were also significant. Exclu ion of parental generation and the use of Method 3 is, therefore advocated. 2 rr2gf (2 cr2g t- (l"2s) ratio revealed preponderance of non-additive gene action for the character studied_ Parent T 59 was found to be the best general combiner. The crossess RL III x T 6342, R LM 240 x RLM 564 and R LM 528 x T 6342 appeared (0 be the best specific cross combinations. In order to exploit non-additive gene effects. population breeding approach such as recurrent selection, diallel selection mating system has been suggested.